Markfysikaliska och kemiska egenskaper i integrerad monitoring områden i förhållande till Sverige nationellt - von Unge, Vilhelm (2017)
Woodland makes up more than two thirds of Sweden’s land area. Forests are of great value for the environment, the Swedish economy and recreational activities. Air pollutants from manmade activities have a negative effect on the wellbeing of forests. Several programs have been created to counteract the impact air pollutants have on forests. Sweden has participated in two monitoring programs of forest soil: BioSoil and Integrerad monitoring (IM). BioSoil is a program on EU level and in the Swedish participation 786 soil profiles were examined. IM is conducted at four forest ecosystems: Gårdsjön, Aneboda, Kindla and Gammtratten. The aim of the program is to increase the understanding of processes in forests soils that are affected by air pollutants. To determine how representative IM is for Swedish forest soil a comparison of several soil variables were conducted between selected soil profiles in the different IM areas with BioSoil, which is thought to have a good representation of Swedish forest soil.